Tinjauan Hukum Terhadap Pertimbangan Hakim Dalam Penetapan Izin Permohonan Perkawinan Beda Agama di Indonesia - Ananda Reicardo; Mia Hadiati (Universitas Ekasakti, 2024)
The development of culture in society has various impacts including on social life, such as the rise of interfaith marriages in Indonesia. Generally, interfaith marriages are not common in Indonesian society because marriages in Indonesia are very thick with religious and ethnic rules which often cause conflicts and problems in the family aspect, the Marriage Law also emphasizes that marriage is considered valid, if it is carried out according to each religion or belief that has agreed. As a result of this provision, interfaith marriages are often not allowed because they are not permitted according to religious provisions. In this modern era, interfaith marriages do not yet have special regulations so that there is no clarity on the rules of marriage validity and child inheritance in interfaith marriages. Therefore, this research will conduct a legal review of the granting of a permit for an application for an interfaith marriage. This normative juridical research uses secondary data supported by the results of interviews which will be analyzed qualitatively and described descriptively. The results of this study indicate that the granting of permission for interfaith marriages is not in accordance with the theory of legal certainty because the Marriage Law and KHI do not allow interfaith marriages or if both religions of the bride and groom do not allow it.